Inteligencia emocional y su relación con el rendimiento académico, en el área de inglés, en estudiantes de secundaria - Herrera Fasabi, Ingrid Susan (2010)
The research had as its aim to see about the fink that exist between the emotional intelligence and the academic performance in the realm of the English language in flfth grade high school students of the educational ínstitution "Cieofe Arevalo del Aguilan of the district of La Banda de Shilcayo in 2010. The hypothesis has been formulated that there's a positiva Jink between the emotional intelligence and academic performance. The sample was made of about 111 students. The research is a correlation like of the predíctive level and a transactional correctionat design. The collection ,of data was canied out applying the inventory of the Baron's intelligence (HOJST); and a collection data card; about the academic performance. The results of the data processed concruded regarding the coefficient of correlation of Pearson -0, 08 exists a negativa link between emotional intelligence and the academic performance.